1998
DOI: 10.1128/aem.64.10.3648-3655.1998
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio cholerae O1 Strain TSI-4 Produces the Exopolysaccharide Materials That Determine Colony Morphology, Stress Resistance, and Biofilm Formation

Abstract: Vibrio cholerae O1 strain TSI-4 (El Tor, Ogawa) can shift to a rugose colony morphology from its normal translucent colony morphology in response to nutrient starvation. We have investigated differences between the rugose and translucent forms of V. cholerae O1 strain TSI-4. Electron microscopic examination of the rugose form of TSI-4 (TSI-4/R) revealed thick, electron-dense exopolysaccharide materials surrounding polycationic ferritin-stained cells, while the ferritin-stained material was absent around the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
0
7

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 216 publications
(110 citation statements)
references
References 45 publications
(41 reference statements)
3
100
0
7
Order By: Relevance
“…In our studies [31,32], V. cholerae O1 strain TSI-4 and V. cholerae O139 strain MO10 could shift to a rugose colony morphology ( Fig. 1) associated with the expression of amorphous extracellular polysaccharides (EPSs) in response to nutrient starvation.…”
Section: Bacterial Surface Characteristics and The Role Of An Extracementioning
confidence: 60%
See 3 more Smart Citations
“…In our studies [31,32], V. cholerae O1 strain TSI-4 and V. cholerae O139 strain MO10 could shift to a rugose colony morphology ( Fig. 1) associated with the expression of amorphous extracellular polysaccharides (EPSs) in response to nutrient starvation.…”
Section: Bacterial Surface Characteristics and The Role Of An Extracementioning
confidence: 60%
“…Global regulatory mechanisms also adjust EPS synthesis according to the general physiological status of the cell, turning it up under nutritional de¢ciency states or down when carbon and energy must be diverted to growth and repair processes. We have also observed that V. cholerae O1 strain TSI-4 and O139 strain MO10 underwent phase variation, converting from translucent to rugose in M9 salts and back again at a frequency of 1.5U10 35 in L broth [31,32]. These bidirectional switches between the two colony types would favor outgrowth of the variant best adapted to a particular environment.…”
Section: Bacterial Surface Characteristics and The Role Of An Extracementioning
confidence: 65%
See 2 more Smart Citations
“…In cyanobacteria high irradiance of BL may cause photodamage (Ohnishi et al, 2005), but strong BL could not cause photoinhibition when cyanobacteria cells were embedded in a biofilm (Hsieh et al, 2014). In addition to providing protection from BL, biofilms can support the scavenging of reactive oxygen species from the surrounding environment (Bylund et al, 2006), and reduce oxidative stress through altering the structural integrity or surface electrical charge of microbial community structure (Chen et al, 2004;Wai et al, 1998).…”
Section: Discusssionmentioning
confidence: 99%